Spontaneous Rupture of Incisional Hernias at the University of Port Harcourt Teaching Hospital, Nigeria : A Case Series - Wichendu, Promise; Dodiyi-Manuel , A. (British Journal of Healthcare and Medical Research, 2022)
Background: There is paucity of literature about spontaneous rupture of incisional hernia. This is hardly surprising because spontaneous rupture of incisional hernia is uncommon. It is also potentially life threatening, because the ensuing entrapment and tension on bowel mesentery may lead to vasovagal shock or strangulation. The fact that this potential catastrophe is preventable by prompt treatment of the hernia, is instructive. We chronicle a series of four cases managed in our centre over a twenty-year period. Case 1 A 31yr old woman presented to the accident and emergency unit of this institution with intestine protruding through an incisional hernia in the lower abdomen. She had three previous caesarian sections. The eviscerated ileum was about 25 centimeters. Exploratory laparotomy was done after resuscitation and a resection, ileo-ileal anastomosis and vertical mayo’s repair of the hernia were done. Her post-operative period was uneventful. Case 2 A 42-year-old woman was rushed to the accident and emergency department of this institution with small bowel protruding through a previous incisional hernia, she had two previous caesarean sections the last being about six years prior to presentation. She was quickly resuscitated and had an exploratory laparotomy and a resection of the devitalised ileum with primary end to end anastomosis and mayo’s repair of the incisional hernia was done. She had a stormy but good post op recovery. Case 3 A 57-year-old lady presented to the accident and emergency department of the hospital with the complaints of evisceration of a bowel loop about an hour prior to presentation. She has had a previous exploratory laparotomy for typhoid perforation, after which she developed an incisional hernia. She was resuscitated and surgery was performed under general anesthesia. The bowels were viable and was returned to the peritoneal cavity after rinsing with normal saline and mesh repair of the hernia was done. Her post-operative period was uneventful and was discharged on the 8th post-operative day. Case 4 45-year-old woman presented to the surgical emergency with a loop of bowel protruding out through abdominal-wall defect in previous scar. she had undergone total abdominal hysterectomy and bilateral salpingo-oophorectomy 6 years earlier. About 28 cm of small intestinal loop was protruding through this defect and this loop was congested, haemorrhagic, but viable. It was quickly rinsed with saline and covered with saline soaked gauze. She had an emergency exploratory laparotomy. The eviscerated bowel was washed with normal saline before repositioning it into the peritoneal cavity. Prolene mesh was used for an on lay repair. The patient made an uneventful recovery CONCLUSION: Rupture of an incisional hernia is a potentially fatal condition. Prevention by prompt repair of incisional hernias as they occur is the best option to prevent its occurrence.